First line of defence: Skin microbiota may protect anurans from infective larval lungworms. (April 2021) - Christian, Keith; Shine, Richard; Day, Kimberley A.; Kaestli, Mirjam; Gibb, Karen; Shilton, Catherine M.; Brown, Gregory P.
Abstract: Functional roles of the rich microbiota of the skin are not fully understood, but include protection against microbial diseases and other environmental challenges. In experimental studies, we show that reducing the microbiota from cane toad ( Rhinella marina ) skin by gently wiping with absorptive gauze resulted in threefold higher rates of infection by lungworms ( Rhabdias pseudosphaerocephala ) following standardised exposure to infective skin-penetrating larvae. Higher concentrations of microbial DNA were associated with lower rates of lungworm entry. Our data suggest that microbial activity on the anuran skin comprises an important line of defence against attack by macroparasites as well as by fungi and other microbes. Highlights: Reduced microbiota on toad skin resulted in higher rates of infection by lungworms. Higher concentrations of microbial DNA were associated with lower infection rates. Microbes on skin may be first line of defence against parasites as well as disease.